Вы находитесь на странице: 1из 27

# Boardworks Ltd 2005 1 of 27

These icons indicate that teachers notes or useful web addresses are available in the Notes Page.
This icon indicates the slide contains activities created in Flash. These activities are not editable.
For more detailed instructions, see the Getting Started presentation.
Boardworks Ltd 2005 1 of 27
AS-Level Maths:
Core 2
for Edexcel
C2.1 Algebra and
functions
Boardworks Ltd 2005 2 of 27
C
o
n
t
e
n
t
s

Boardworks Ltd 2005 2 of 27
Dividing polynomials
The Remainder Theorem
The Factor Theorem
Examination-style questions
Dividing polynomials
Boardworks Ltd 2005 3 of 27
Multiplying polynomials
Two polynomials are multiplied together and the
resulting polynomial is x
3
+ x
2
10x + 8.
One of the polynomials is (x + 4). What is the other?
x + 4 is a linear polynomial. To obtain a cubic polynomial as
required we need to multiply it by a quadratic of the form
ax
2
+ bx + c.
We can write (x + 4)(ax
2
+ bx + c) x
3
+ x
2
10x + 8.
This is an example of an identity as shown by the symbol .
An identity is true for all values of x.
Since the expression on the left hand side is equivalent to the
expression on the right hand side, the coefficients of x
3
, x
2
, x and
the constant must be the same on both sides.
Boardworks Ltd 2005 4 of 27
Equating coefficients
We can use the method of equating coefficients to find the
values of a, b and c in the identity
Multiplying out:
(x + 4)(ax
2
+ bx + c) x
3
+ x
2
10x + 8
Equating the coefficients of x
3
gives
ax
3
+ bx
2
+ cx + 4ax
2
+ 4bx + 4c x
3
+ x
2
10x + 8
ax
3
+ (b + 4a)x
2
+ (c + 4b)x + 4c x
3
+ x
2
10x + 8
a = 1
Equating the coefficients of x
2
gives
b + 4a = 1
But a = 1 so b + 4 = 1
b = 3
Boardworks Ltd 2005 5 of 27
Equating coefficients
Equating the coefficients of x gives
We can equate the constants to check this value:
4c = 8
Substituting a = 1, b = 3 and c = 2 into
c + 4b = 10
But b = 3 so c 12 = 10
c = 2
c = 2
(x + 4)(ax
2
+ bx + c) x
3
+ x
2
10x + 8
Gives the solution
(x + 4)(x
2
3x + 2) = x
3
+ x
2
10x + 8
What is x
3
+ x
2
10x + 8 divided by x + 4?
Boardworks Ltd 2005 6 of 27
Dividing polynomials
Suppose we want to divide one polynomial f(x) by another
polynomial of lower order g(x).
g(x) will divide exactly into f(x). In this case, g(x) is a factor
of f(x) and the remainder is 0.
There are two possibilities. Either:
g(x) will leave a remainder when divided into f(x).
We can use either of two methods to divide one polynomial by
another. These are by:
using long division, or
writing an identity and equating coefficients.
Boardworks Ltd 2005 7 of 27
Dividing polynomials by long division
Using long division
The method of long division used for numbers can be applied
to the division of polynomial functions.
Lets start by looking at the method for numbers.
For example, we can divide 5482 by 15 as follows:
This tells us that 15 divides into 5482
365 times, leaving a remainder of 7.
We can write
or 5482 = 15 365 + 7
The
dividend
5482 15 = 365 remainder 7
The
divisor
=
The
quotient

The
remainder
+
5 15 4 8 2
3
4 5
9 8
6
9 0
8 2
5
7 5
7
Boardworks Ltd 2005 8 of 27
Dividing polynomials by long division
We can use the same method to divide polynomials.
For example:
What is f(x) = x
3
x
2
7x + 3 divided by x 3?
x
3
x
2
7x + 3 x 3
x
3
3x
2
2x
2
7x
+ 2x
2x
2
6x

x + 3
1
x + 3
0
This tells us that x
3
x
2
7x + 3
divided by x 3 is x
2
+ 2x 1.
The remainder is 0 and so x 3
is a factor of f(x).
We can write
x
3
x
2
7x + 3 =(x 3)(x
2
+ 2x 1)
3 2
2
7 +3
= +2 1
3
x x x
x x
x

x
2
or
Boardworks Ltd 2005 9 of 27
Dividing polynomials by long division
Here is another example:
What is f(x) = 2x
3
3x
2
+ 1 divided by x 2?
2x
3
3x
2
+ 0x + 1 x 2
2x
3
4x
2
x
2
+ 0x
+ x
x
2
2x

2x + 1
+ 2
2x 4
5
This tells us that 2x
3
3x
2
+ 1
divided by x 2 is 2x
2
+ x + 2
remainder 5.
There is a remainder and so x 2
is not a factor of f(x).
We can write
2x
3
3x
2
+ 1 =(x 2)(2x
2
+ x + 2) + 5
2x
2
3 2
2
2 3 1
2
2
5
2
2
x x
x
x x
x
+
= + + +

or
Boardworks Ltd 2005 10 of 27
Dividing polynomials
Using the method of equating coefficients
Polynomials can also be divided by constructing an appropriate
identity and equating the coefficients. For example:
What is f(x) = 3x
2
+ 11x 8 divided by x + 5?
We can write f(x) = 3x
2
+ 11x 8 in terms of a quotient and a
remainder as follows:
3x
2
+ 11x 8 = (x + 5)(quotient) + (remainder)
To obtain a quadratic polynomial the quotient must be a linear
polynomial of the form ax + b.
We can write the following identity:
3x
2
+ 11x 8 (x + 5)(ax + b) + r
Boardworks Ltd 2005 11 of 27
Dividing polynomials
Expanding: 3x
2
+ 11x 8 ax
2
+ bx + 5ax + 5b + r
ax
2
+ (b + 5a)x + 5b + r
Equating the coefficients of x: b + 5a = 11
But a = 3 so b + 15 = 11
b = 4
Equating the coefficients of x
2
: a = 3
Equating the constants: 5b + r = 8
But b = 4 so 20 + r = 8
r = 12
We can use these values to write
3x
2
+ 11x 8 (x + 5)(3x 4) + 12
3x
2
+ 11x 8 divided by x + 5 is 3x 4 remainder 12.
So
Boardworks Ltd 2005 12 of 27
C
o
n
t
e
n
t
s

Boardworks Ltd 2005 12 of 27
The Remainder Theorem
Dividing polynomials
The Remainder Theorem
The Factor Theorem
Examination-style questions
Boardworks Ltd 2005 13 of 27
The Remainder Theorem
Consider again the example where f(x) = 3x
2
+ 11x 8 divided
by x + 5.
f(5) = 3(5)
2
+ 11(5) 8
= 75 55 8
= 12
Can you explain why this number should be the same as
the remainder when f(x) = 3x
2
+ 11x 8 divided by x + 5?
f(x) = (x + 5)(quotient) + (remainder)
If x = 5 then f(5) = (5 + 5)(quotient) + (remainder)
= 0 + (remainder)
So when f(x) is divided by (x + 5), f(5) = the remainder.
Find the value of f(5).
Boardworks Ltd 2005 14 of 27
The Remainder Theorem
When a polynomial f(x) is divided by (x a),
the remainder is f(a).
This is called the Remainder Theorem.
We can use this theorem to find the remainder when a
polynomial is divided by an expression of the form (x a).
For example:
Find the remainder when the polynomial
f(x) = x
3
3x
2
8x + 5 is divided by (x + 2).
Using the Remainder Theorem, the remainder is given by f(2).
f(2) = (2)
3
3(2)
2
8(2) + 5
= 8 12 + 16 + 5
= 1
Boardworks Ltd 2005 15 of 27
C
o
n
t
e
n
t
s

Boardworks Ltd 2005 15 of 27
The Factor Theorem
Dividing polynomials
The Remainder Theorem
The Factor Theorem
Examination-style questions
Boardworks Ltd 2005 16 of 27
The Factor Theorem
If (x a) is a factor of a polynomial f(x) then f(a) = 0.
The converse is also true:
If f(a) = 0 then (x a) is a factor of a polynomial f(x).
Suppose that when a polynomial f(x) is divided by an
expression of the form (x a) the remainder is 0.
What can you conclude about (x a)?
If the remainder f(a) is 0 then (x a) is a factor of f(x).
This is the Factor Theorem:
Boardworks Ltd 2005 17 of 27
The Factor Theorem
(x + 2) is a factor of 3x
2
+ 5x 2 if f(2) = 0
f(2) = 3(2)
2
+ 5(2) 2
= 12 10 2
= 0 as required.
We can write 3x
2
+ 5x 2 = (x + 2)(ax + b)
Use the Factor Theorem to show that
(x + 2) is a factor of f(x) = 3x
2
+ 5x 2.
Hence or otherwise, factorize f(x).
By inspection a = 3 and b = 1
And so 3x
2
+ 5x 2 = (x + 2)(3x 1)
Boardworks Ltd 2005 18 of 27
Factorizing polynomials
The Factor Theorem can be used to factorize polynomials by
systematically looking for values of x that will make the
polynomial equal to 0. For example:
Factorize the cubic polynomial x
3
3x
2
6x + 8.
Let f(x) = x
3
3x
2
6x + 8.
f(x) has a constant term of 8. So possible factors of f(x) are:
(x 1), (x 2), (x 4) (x 8) or
f(1) = 1 3 6 + 8 = 0 (x 1) is a factor of f(x).
f(1) = 1 3 + 6 + 8 0 (x + 1) is not a factor of f(x).
f(2) = 8 12 12 + 8 0 (x 2) is not a factor of f(x).
Boardworks Ltd 2005 19 of 27
Factorizing polynomials
f(2) = 8 12 + 12 + 8 = 0 (x + 2) is a factor of f(x).
f(4) = 64 48 24 + 8 = 0 (x 4) is a factor of f(x).
We have found three factors and so we can stop.
x
3
3x
2
6x + 8 = (x 1)(x + 2)(x 4)
The given polynomial can therefore be fully factorized as:
Factorize f(x) = x
3
+ 1
f(x) has a constant term of 1 so the only possible factors of f(x)
are (x 1) or (x + 1).
f(1) = 1 + 1 0 (x 1) is not a factor of f(x).
f(1) = (1)
3
+ 1 = 0
(x + 1) is a factor of f(x).
Boardworks Ltd 2005 20 of 27
The factor theorem
We dont know any other factors but we do know that the
expression x + 1 must be multiplied by a quadratic expression
to give x
3
+ 1. We can therefore write
x
3
+ 1 = (x + 1)(ax
2
+ bx + c)
We can see immediately that a = 1 and c = 1 so
x
3
+ 1 = (x + 1)(x
2
+ bx + 1)
= x
3
+ bx
2
+ x + x
2
+ bx + 1
= x
3
+ (b + 1)x
2
+ (b + 1)x + 1
Equating coefficients of x
2
gives
b + 1 = 0
b = 1
So x
3
+ 1 can be fully factorized as
x
3
+ 1 = (x + 1)(x
2
x + 1)
Boardworks Ltd 2005 21 of 27
Extending the remainder and factor theorems
So, in general:
When a polynomial f(x) is divided by (ax b),
.
b
f
a
| |
|
\ .
the remainder is
Suppose we want to know the remainder when a polynomial
f(x) is divided by an expression of the form (ax b). We can
write
f(x) = (ax b)(quotient) + (remainder)
We can eliminate the quotient by choosing x so that
ax b = 0
=
b
x
a
ax = b
Boardworks Ltd 2005 22 of 27
Extending the remainder and factor theorems
Find the remainder when the polynomial
f(x) = 2x
3
6x + 1 is divided by (2x 1).
Using the Remainder Theorem, the remainder is given by
1
2
( ). f
3
1 1 1
2 2 2
( ) = 2( ) 6( ) +1 f
1
4
= 3+1
3
4
= 1
We can similarly extend the Factor Theorem to include factors
of the form (ax b).
= 0 ( ) is a factor of ( )
b
f ax b f x
a
| |

|
\ .
We can write:
Where means implies and is implied by.
Boardworks Ltd 2005 23 of 27
C
o
n
t
e
n
t
s

Boardworks Ltd 2005 23 of 27
Examination-style questions
Dividing polynomials
The Remainder Theorem
The Factor Theorem
Examination-style questions
Boardworks Ltd 2005 24 of 27
Examination-style question
p(x) = 4x
3
+ ax
2
+ bx 15
p(x) leaves a remainder of 27 when divided by x 2.
x + 1 is a factor of p(x).

a) Find the values of a and b and hence write p(x) in full.
b) Express p(x) as a product of linear factors.
c) Sketch the graph of y = p(x) clearly indicating where the
graph crosses the coordinate axes.
a) Using the remainder theorem:
p(2) = 32 + 4a + 2b 15 = 27
4a + 2b = 10
2a + b = 50
1
Boardworks Ltd 2005 25 of 27
Examination-style question
Using the factor theorem:
p(1) = 4 + a b 15 = 0
a b = 19
1
1 2
3a = 24
a = 8
b = 11
So p(x) can be written in full as
p(x) = 4x
3
+ 8x
2
11x 15
Boardworks Ltd 2005 26 of 27
Examination-style question
b) We know that x + 1 is a factor of p(x) so we can write
4x
3
+ 8x
2
11x 15 (x + 1)(ax
2
+ bx + c)
By inspection
a = 4 and c = 15
Equating the coefficients of x:
11 = c + b
11 = 15 + b
b = 4
p(x) = 4x
3
+ 8x
2
11x 15 = (x + 1)(4x
2
+ 4x 15) So
Factorizing:
p(x) = 4x
3
+ 8x
2
11x 15 = (x + 1)(2x + 5)(2x 3)
Boardworks Ltd 2005 27 of 27
Examination-style question
c) The graph of y = p(x) crosses the x-axis when
4x
3
+ 8x
2
11x 15 = 0
(x + 1)(2x + 5)(2x 3) = 0
That is when x = 1, x = 2.5, and x = 1.5
The graph of y = p(x) crosses the y-axis when
y = 15
Also the coefficient of x
3
is positive
so the graph is -shaped:
x
y
15
1.5 1 2.5